Chemical variables - lake from Tarfalasjön, water sample, 2018-04-07–2018-09-05 - Tarfala Research Station (Stockholm University, 2025)
Manual grab samples for chemical analysis are taken from the lake on a biweekly basis during ice-free conditions, and on a monthly basis during ice cover conditions. At the central lake sampling location water samples are collected from both epi- and hypolimnion during periods of stratification.
Tarfala Research Station (2025). Chemical variables - lake from Tarfalasjön, water sample, 2018-04-07–2018-09-05 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/9PDsvtEpxLuRfLymt_yM4JPc
Keywords: Tarfala Research Station; Lake; Time instant; Time instant; pH; pH; Electrical conductivity; Electrical conductivity; Dissolved organic carbon; Dissolved organic carbon; Total nitrogen; Total nitrogen; Phosphate-P; Phosphate-P; Ammonium-N; Ammonium-N; Nitrite-N/Nitrate-N; Nitrite-N/Nitrate-N; Sulphate-S; Sulphate-S; Fluorine; Fluorine; Chlorine; Chlorine; Proportion Oxygen-18 in Water; Proportion Oxygen-18 in Water; Proportion Deuterium in Water; Proportion Deuterium in Water; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap